PROFESSIONAL IN EDUCATIONAL PROCESSES IMPORTANT ASPECTS OF COMPETENCE ORGANIZATION (World Bulletin of Social Sciences, 2024)
Today, the problem of improving the competence of professors and teachers, constantly and consistently increasing, which is considered the most important element of the system for organizing the educational process and ensuring the quality of education, is of particular relevance. At the same time, it is noted that there is a need to” improve the process and means of assessing the quality of Education, put into practice mechanisms that allow you to determine the results achieved."